TRIAS PEMBANGUNAN MELALUI SINERGI MODERASI, UMKM, DAN GIZI DI PEMATANG ASILOM - Inayah, Nurul; Zahra Nabila Iqbal; Handra Humala Dalimunthe; Maullida Hayati; Ruri Aldisyah Siregar (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2025)
The Community Service Program (KKN) has a strategic role in community empowerment. Religious moderation, MSME innovation, and stunting nutrition are three excellent work programs of UINSU 2025 KKN students in Pematang Asilom Village. The purpose of this research is to instill harmony and unity within the scope of religious moderation, provide innovation for MSMEs, and nutritional interventions to prevent stunting cases. This research uses a descriptive qualitative method in which observation, interviews, and documentation are used as data collection techniques. In this service activity, KKN UINSU 2025 students have tried to establish harmony between neighborhoods in Pematang Asilom village, provide innovations in the form of ideas for selling spinach chips and making Qris as a lagging work program, and participate in collaborating with the puskesmas to prevent stunting. This research concludes that these three excellent programs can realize village welfare if implemented sustainably. Such as establishing harmony in the context of religious moderation, bringing innovation to MSMEs in line with the technological era, and paying attention to nutrition for stunting prevention.